TINJAUAN KRIMINOLOGIS TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA DAN PENANGGULANGANNYA (Studi Kasus di Unit Perlindungan Perempuan dan Anak Polres Malang ) - praditya alif ratanto (Fakultas Hukum Universitas Islam Malang, 2021)
Domestic violence in 2020 has increased, especially in the Malang Regency area. In Law Number 23 of 2004 concerning the Elimination of Domestic Violence, it discusses legal protection for victims and sanctions for perpetrators. This study discusses what factors cause cases of domestic violence, what forms of violence often occur, what efforts have been made to deal with cases of domestic violence, and what impacts occur as a result of domestic violence. The research method used is qualitative research with case studies conducted at the Malang Police Criminal Investigation Unit with three components, namely data reduction, data presentation and drawing conclusions or levers. The results of the study indicate that there are internal and external factors that trigger acts of domestic violence, in the form of physical acts that often occur. Several efforts have been made, namely pre-emptive, preventive, repressive efforts and will have an impact on victims and perpetrators of domestic violence.